An improved optical length research on the physical boundary of particle-dispersed fuel - Liu, Pengfei; Chen, Yuqing; Li, Song; Lou, Lei (Frontiers in Energy Research, 2024)
The Volumetric Homogenization Method (VHM) is one of the most commonly used methods for neutronics calculation in reactors or components. However, the use of VHM for the Double-Heterogeneous(DH) System may lead to a large deviation in reactivity calculation. The deviation of DH System using the VHM can be expressed by the theoretically modified optical length. When the theoretically modified optical length is less than 10 -4 , the deviation caused by the VHM will be less than 100pcm. This paper points out that the existing theoretically modified optical length for some cases of DH systems is not accurate, and this method is only for pin cell. In this paper, by calculating a series of DH models and their corresponding VHM models, it is found that the water-uranium ratio and the shape of fuel region seriously affects the reactivity calculation deviation of particle-dispersed fuel, the original modified optical length does not take this into account, resulting in unacceptable errors. On this basis, the application of optical length to physical boundaries for DH system is further discussed and the shape correction factor is taken into consideration. Therefore, an improved optical length is proposed, which greatly expands the range of application of the physical boundary judgment methods for the double heterogeneity of dispersed particle fuel. The numerical results show that the accuracy of the improved optical length in defining the physical boundary of double heterogeneous system is higher than the theoretically modified optical length.